Renovasi Pola Pikir Implimentasi CSR Menuju Metamorfosis Perekonomian Indonesia - Elizabeth Sugiarto Dermawan (Jurnal Ekonomi, 2010)
The way of thinking Corporate Social Responsibility (CSR) implementation in Indonesia should be renovated to make a better change for the economic growth. Most CSR activities is just a charity and are often seen as a burden that impedes the company growth, and may impact the growth of the Indonesian economy. As reported in CSR Indonesia Newsletter vol.3 (2009) under Indonesian law, private companies are obliged to carry out CSR programs and State-owned companies are also bound by law to carry out CSR programs known as Partnership Program and Community Development (PKLB) although that is a good policy most companies currently view CSR as an obligation rather than a responsibility. Based on that reality, this article tries to re-motivated especially the reader and in general people in this country who become stakeholders of a company have to be realized that this is the time to change the bad image of CSR. Stakeholders' perception in the area of positioning the company image is an important part of business sustainability.